Weitzman's approach and conservation of breed diversity: An application to African cattle breeds - Reist-Marti, S.B.; Simianer, H.; Gibson, John P.; Hanotte, Olivier H.; Rege, J.E.O. (Wiley, 2003)
To evaluate the Weitzman approach for assessing alternative conservation strategies for breed ( population ) diversity, we used genetic distance measures between 49 African cattle breeds divided into two groups of 26 taurine ( Bos taurus ) and sanga ( Bos taurus×Bos indicus ) breeds and 23 zebu ( Bos indicus ) and zenga ( sanga ×Bos indicus ) breeds. The derived maximum-likelihood trees clearly displayed the geographic distribution and the zebu-taurine admixture of the breeds. We developed a novel scheme to estimate the extinction probability for each breed which considered total population size, change of population size over the last 10 years, distribution of the breed, risk of indiscriminate crossing, organization among farmers, establishment of conservation schemes, political situation of the countries, special traits, sociocultural importance, and reliability of information. This scheme yielded reasonable estimates of extinction probabilities for the analyzed breeds, which were significantly influenced by the population size and its recent change, distribution of the breed, organization among farmers, establishment of conservation schemes, and reliability of information. The average extinction probability over all breeds and for each breed group was around 48%. Diversity in the zebu-zenga group was only half the diversity in the taurine-sanga group, mainly because of the lower number of breeds and their genetic origin. For both groups, the expected diversity after 20–50 years was about half the current diversity, and the coefficient of variation was about 20%. Our results suggest that the optimum conservation strategy is to give priority to those breeds with the highest marginal diversity, rather than to the most endangered breeds; thus, Madagascar Zebu and Muturu should be given conservation priority in their respective groups. Our study demonstrates that efficient conservation of genetic diversity with limited funds has to take genetic and nongenetic factors into account. Nongenetic factors are accounted for within our scheme to derive extinction probabilities. Within-breed and within-population diversity are not accounted for. Extending Weitzman's basic approach accordingly could yield an effective methodology for determining conservation strategies under highly varying circumstances and for many species, including wild organisms.